2018
DOI: 10.1111/cea.13129
|View full text |Cite
|
Sign up to set email alerts
|

Complex association patterns for inflammatory mediators in induced sputum from subjects with asthma

Abstract: Sputum cytokines, chemokines and growth factors were increased in severe asthma, primarily with increased neutrophils. Factor analysis identified complex inflammatory protein interactions, suggesting airway inflammation in asthma is characterized by overlapping immune pathways. Thus, focus on a single specific inflammatory mediator or pathway may limit understanding the complexity of inflammation underlying airway changes in asthma and selection of appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 43 publications
5
39
0
5
Order By: Relevance
“…Several studies have reported increased eosinophils and/or neutrophils associated with severe asthma, although different cut‐offs for the definition of increased levels were used in these studies; and in line with previous findings, we found eosinophilia to be more common than neutrophilia. However, while blood neutrophils significantly separated severe asthma from other asthma in our study, blood eosinophils only tended to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported increased eosinophils and/or neutrophils associated with severe asthma, although different cut‐offs for the definition of increased levels were used in these studies; and in line with previous findings, we found eosinophilia to be more common than neutrophilia. However, while blood neutrophils significantly separated severe asthma from other asthma in our study, blood eosinophils only tended to do so.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both low type 2 and high type 2 inflammatory conditions augment hyperresponsiveness. However, the complexity of inflammatory processes causing airway changes in asthma remains a challenge [17,18]. LMW toluene diisocyanate (TDI; 174.2 g/mol) is one of the most common causes of OA worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects, sputum induction and processing, and Luminex analysis. Patients with mild to severe asthma were comprehensively characterized according to the NHLBI SARP phenotype protocol at Wake Forest School of Medicine as previously described (58), and a description of this cohort was recently reported (59). The sputum induction method was adopted from the NHLBI Asthma Clinical Research Network and used in SARP (60).…”
Section: Methodsmentioning
confidence: 99%